Emotional Distress of Patients at End-of-Life and Their Caregivers: Interrelation and Predictors - Soto-Rubio, Ana; Perez-Marin, Marian; Tomas Miguel, Jose; Barreto Martin, Pilar (Frontiers in Psychology, 2018)
Background: Patients at the end-of-life and their families experience a strong emotional impact. The wellbeing of the patient at the end-of-life and their family caregiver are related. Aim: to explore the elements related with the emotional wellbeing of patients with and without cognitive impairment at the end-of-life and that of their primary family caregivers. Design: Cross- sectional study. Participants: data was collected from 202 patients at the end of life with different diagnosis (COPD, cancer and frail elderly) as well as from their respective 202 primary family caregivers. Results: Structural equation models indicated that the emotional state of the patients was best predicted by their functional independence and the burden of their family caregivers. At the same time, the emotional state of the primary family caregiver was predicted by their burden and not by the cognitive state or the functional independence of the patient. Nevertheless, the burden of the family caregiver, which is the only variable predicting both the emotional state of the patient and that of the caregiver, was directly related with the functional independence of the patient and indirectly with the patient’s cognitive state. Conclusions: The burden of the family caregiver stands out as a key factor in the reduction of the emotional distress of patients at the end-of-life –whether or not they present significant cognitive impairment- and that of their family caregivers.